NECESIDAD DE ESTABLECER UNA JORNADA MÁXIMA DE TRABAJO PARA LAS TRABAJADORAS DE SERVICIO DOMÉSTICO, QUE LABORAN BAJO LA MODALIDAD PUERTAS ADENTRO - Chicaiza Guamo, Ana María (2016)
The thesis that next have developed he/she has as fundamental purpose to outline a solution proposal to the reality in that the abuse and the labor exploitation that face the great majority of those used live since you tame that he/she works inside under the modality of doors, it should be a social problem that requires of some urgent solution. With these antecedents it is necessary to appeal to the legal means that try to aid the integrity of people and consequently the Right to the work that consecrates the Constitution, fact that should mean an important evolution in the development of the contemporary constitutional State, expert as State dedicated to guarantee the protection and validity of the human rights Of there also drift the responsibility that has the State of offering legal guarantees that sanction the labor exploitation that is humiliating in our times because most of the employees have between 21 and 30 years of age, they are single or divorced mothers and they should maintain their children economically. It is for this reason that he/she should settle down the normative one properly regulated so that a regulation mark that allows the sanction to these abusive acts that you/they enjoy impunity settles down. So that a form of avoiding the abuse and the labor exploitation that the domestic employees that work door inside face is that the competent organs look for legal mechanisms that it allows them to control, and to sanction these abuses that the employers comment.